Detection of the Effectiveness Metabolic Production of Pseudomonas Fluorescence towards Inhibition of Growth Fusarium Graminearum and Production to Zeralenone - Wisam Jasim Abed Ali (Journal of Global Pharma Technology, 2019)
The study aimed to conduct a survey of fungi associated with the rice crop and focus on Fusarium graminearum and the detection of its ability to produce of zeralenone. 50 samples of local and imported rice were collected in the city of Diwaniyah. The results showed a wide spread of fungi in local and imported rice samples, where the fungi are isolated Aspergillus spp, Fusarium spp., Alternaria spp. , Penicillium spp., Rhizopus spp. and Mucor spp. by ratio (32,24,20,8,8,8) %. Results of ELISA examination were shown four species of Fusarium graminearum were produced of zeralenone by rate 33.3%. The results showed the effectiveness of metabolic products of bacteria showed high efficacy to inhibit the growth of F. graminearum and inhibit the production of zeralenone at four concentrations of metabolic products from Pseudomonas fluorescence (250, 500, 750, 1000) mg/l.Keywords: Fusarium graminearum, Zeralenone, Pseudomonas fluorescence.